The Relationship Between Innovative Learning Management of a Love-Based Curriculum and the Improvement of English Communication Competence Among Madrasah Aliyah Students - Mujahidin, Irfan; Sulaeman, Iskandar; Qonitah, Mona; Siskawati, Isna (Al Irsyad: Jurnal Studi Islam, 2025)
The English communication competence of Madrasah Aliyah students remains low due to speaking anxiety, limited vocabulary, lack of authentic practice, and a social environment that does not support English language culture. This study analyses the relationship between innovative learning management based on the Love-Based Curriculum (KBC) and students' English communication competence. A quantitative correlational approach was employed by distributing questionnaires to 40 students. Data analysis using SPSS revealed a correlation coefficient of 0.872 and a determination value of 0.761, indicating a powerful positive relationship with a contribution of 76.1%. These findings confirm that love-based learning effectively creates a safe and supportive classroom environment, reduces speaking anxiety, and increases students' confidence in expressing ideas in English. The study implies a necessary shift in teachers' roles to become value facilitators and holistic development mentors. In conclusion, implementing KBC strengthens English competence while fostering character development, collaboration, and intercultural communication skills essential in the global era.